2014
DOI: 10.1080/00028487.2014.949012
|View full text |Cite
|
Sign up to set email alerts
|

Determination of River Herring Natal Origin using Otolith Chemical Markers: Accuracy as a Function of Spatial Scale and Choice of Markers

Abstract: We investigated the spatial and temporal accuracy of otolith chemistry for distinguishing populations (and subpopulations) of anadromous river herring (Alewife Alosa pseudoharengus and Blueback Herring A. aestivalis) from New York watersheds. Water chemistry of selected analytes (Sr:Ca, Ba:Ca, 87:86Sr, and δ18O) differed spatially and interannually among sites within the Hudson River as well as between the Hudson River and Long Island estuaries. Otolith chemical markers for juvenile river herring differed sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Calcium concentrations in the water during 2009 and 2010 were consistently higher at all Hudson River sampling locations than at Long Island estuaries (Figure 3 Otolith Mn:Ca ratios were generally higher in fish from Long Island, where water samples had lower Ca concentrations and higher Mn concentrations, than in fish from the Hudson River watershed. Despite these general differences, the otolith Mn concentration did not differ enough among sites for use in natal assignment with other otolith markers (Sr:Ca, Ba:Ca, 87:86 Sr, and d 18 O) via quadratic discriminant function analysis (Turner and Limburg 2014).…”
Section: Water and Otolith Chemistrymentioning
confidence: 83%
See 2 more Smart Citations
“…Calcium concentrations in the water during 2009 and 2010 were consistently higher at all Hudson River sampling locations than at Long Island estuaries (Figure 3 Otolith Mn:Ca ratios were generally higher in fish from Long Island, where water samples had lower Ca concentrations and higher Mn concentrations, than in fish from the Hudson River watershed. Despite these general differences, the otolith Mn concentration did not differ enough among sites for use in natal assignment with other otolith markers (Sr:Ca, Ba:Ca, 87:86 Sr, and d 18 O) via quadratic discriminant function analysis (Turner and Limburg 2014).…”
Section: Water and Otolith Chemistrymentioning
confidence: 83%
“…On Long Island, Alewives were collected once per summer in 2009 and 2010 (Blueback Herring do not spawn in Long Island rivers; Figure 1C). In total, 140 Alewives and 48 Blueback Herring were included in analyses; 138 Alewives and 143 Blueback Herring from our previous study (Turner and Limburg 2014) were not included here because otolith increments were destroyed during preparation, no Mn:Ca shifts were observed, or shifts in Mn:Ca and daily growth corresponded with shifts in Sr:Ca and Ba:Ca. Sagittal otoliths were removed, cleaned, and polished to the core prior to chemical analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the information contained within otolith chemistry has been used to infer the stock structure and environmental history of the fish species (Clarke et al 2007;Allen et al 2009;Reis-Santos et al 2018). The otolith chemistry has been effectively used to identify the natal origin or dispersal pattern of a number of marine, freshwater, and anadromous fishes (Schaffler and Winkelman 2008;Zeigler and Whitledge 2010;Turner and Limburg 2014;Bailey et al 2015;Garcez et al 2015). A major disadvantage of using otolith chemistry is the temporal variability in water chemistry within the natal origin of fish populations (Pangle et al 2010).…”
Section: Otolith Chemistrymentioning
confidence: 99%
“…In the present study, Sr:Ca, Ba:Ca, Mg:Ca, Mn:Ca and Rb:Ca levels in the water demonstrated some seasonal variation with most of the element:Ca ratios being higher during the summer period. Intra‐ and interannual variation in water element:Ca ratios has been demonstrated before, and this has been related to varying discharge rates with Sr:Ca and 87 Sr: 86 Sr ratios being higher during the low flow period in summer and autumn (Martin, Bareille, Berail, Pecheyran, et al, 2013; Turner & Limburg, 2014). It has been also found, that during low flow conditions, surface water chemistry is dominated by groundwater and water from lower soil layers where the weathering is more intense, resulting in higher ion concentrations in surface water (Jarvie et al, 2000).…”
Section: Discussionmentioning
confidence: 71%